Program Penerbitan Sertipikat Pendaftaran Tanah Sitematis Lengkap (PTSL) Terhadap KSB di Kota Batam - Padrisan Jamba; Irene Svinarky (Prosiding, 2018)
Problem that is at Batam's City one of it is land. Land that researcher team means which is land which had by society that stills to have narrow science to prevailing order. Mostly society which its earth was Land Certificated at City Batam shall follow earlier rule already at rule by Otorita Batam. Land office in Batam constitutes commisioned institution publish Land Certificate releasing afters catch waiver, its determination location and requisite that gave by Otorita Batam was accomplished by society for earlier get Kavling's Place Contract Available Build. Therefore therefore Researcher Team interests to lift Land Certificate Program title Cadastral Fledged Sitematis (PTSL) To Kavling Available Build That Are On Batam's City. There is aim even this research is as follows: To know If Kavling Available Build (KSB) can publish serifikatnya. Observational method that Researcher Team utilizes which is empirical research by use of primary data source, and secondary data source. This data source is utilized as step gather information source. Observational result that can be pulled this in writing: Kavling Readily Builds is enabled to been published its certificate land, since target from PTSL which did by City land Office Batam until all society which propose PTSL that no more that proposes application, one that has to be remembered by publication target society this certificate not just after long time.